Efektivitas Model PJBL dalam Meningkatkan Keterampilan Komunikasi Sains Siswa Sekolah Menengah Islam Al Amin Islamic School, Terengganu, Malaysia - Hanafi Arbi Wiranata; Hadi Purwanto; Neng Sholihat; Berry Kurnia Vilmala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PJBL) model in improving students' science communication skills in the subject of Natural Sciences (IPA) at the secondary school level. The method used is classroom action research (CAR) with a one-group pre-test–post-test design. The study was conducted through observation of learning activities carried out collectively in the classroom. The results showed that students' communication skills improved from cycle I to cycle II in each indicator: clear voice increased from 45% to 80%, proper grammar usage from 30% to 60%, pleasant facial expressions from 40% to 70%, eye contact with the audience from 38% to 75%, and speech comprehension by the audience from 40% to 70%. In conclusion, the PJBL learning model significantly affects the improvement of science communication skills among students at Al Amin Islamic Secondary School Kemaman, Terengganu. Keywords: Al Amin Islamic School, Instructional Model, Project-Based Learning, Science Communication, Science Learning